(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2017)
A new conical agglutinated foraminifer, Lepinoconus chiocchinii gen n., n. sp. from the lower Campanian shallow-water platform deposits of the Lepini Mountains (central Apennines, Italy), is described. It has a pseudo-keriothecal wall structure, uniserial arrangement of the adult chambers and multiple apertures. The exoskeleton is constituted by beams (main and intercalary) continuous from one chamber to the next, while the endoskeleton bears pillars. The new taxon is included in the Coskinolinidae family. Lepinoconus chiocchinii gen. n., n. sp. is known from southern Italy, Greece and Albania.